SPIDER CRABS OF THE GENERA PARATYMOLUS MIERS, 1879 AND LITOSUS LOH & NG, 1999 FROM LOMBOK ISLAND, INDONESIA (CRUSTACEA, DECAPODA, BRACHYURA, MAJOIDEA, INACHIDAE) - Rahayu, Dwi Listyo (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2011)
A small collection of majoid spider crabs of the genus Paratymolus Miers, 1879, s.l from Lombok Island, Indonesia contains four species namely P. hastatus Alcock (1895), P. coccus Loh & Ng (1999), P. cygnus Loh & Ng (1999), and Litosus sexspinosus (Miers, 1884). Except for L. spinosus, the three other species are new records for Indonesia. Paratymolus coccus is previously known from only female specimens, and the presence of male specimens in the collection studied provides the opportunity to complete the description of male characters. Paratymolus hastatus is reported for the first time outside Indian Ocean and P. cygnus is recorded for the first time after its description.